HUBUNGAN VENTILASI RUMAH, STATUS GIZI DAN KELENGKAPAN IMUNISASI DENGAN KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT (ISPA) DI PRAKTIK MANDIRI BIDAN (PMB) JUNAEDAH DESA MUARABARU KECAMATAN MAKARTI JAYA KABUPATEN BANYUASIN - KHADIJAH, SITI KHADIJAH; Erma Puspita Sari; Rini Gustina Sari; Rizki Amalia (SEKOLAH TINGGI ILMU KESEHATAN INDRAMAYU, 2025)
Acute Respiratory Infection or what is usually called (ARI). When an infection occurs, bacteria and microorganisms enter the human body and also cause symptoms of disease. Acute infection is an infection that lasts for approximately 14 days. The aim of this study was to determine the relationship between house ventilation, nutritional status and completeness of immunization with the incidence of acute respiratory infections in toddlers. This research uses a cross section approach using univariate and bivariate analysis. The results obtained from the 42 respondents studied were 19 respondents 45.2 who experienced ISPA and 23 respondents 54.8 who did not experience ISPA. most of the 18 respondents 42.9 did not meet the requirements for ventilation, 10 respondents 23.8 had poor nutrition and 16 respondents 38.1 had incomplete immunization. Sample determination was taken using total sampling technique. Based on the results of research using the chi-square statistical test, it is known that there is a significant relationship between house ventilation and the incidence of acute respiratory infections (ARI) in children under five, with a P value of 0.001, there is no significant relationship between nutritional status and the incidence of acute respiratory infections ( ARI) in toddlers obtained a p value of 0.143, there was a significant relationship between the completeness of immunization and the incidence of acute respiratory infections (ARI) in toddlers obtained a p value of 0.007. So it can be concluded that there is no relationship between house ventilation, nutritional status and completeness of immunization simultaneously with the incidence of acute respiratory infections (ARI). It is recommended that parents, especially mothers, take better care of the health of their toddlers and the surrounding environment, so that toddlers can avoid ISPA